2011
DOI: 10.5248/116.75
|View full text |Cite
|
Sign up to set email alerts
|

Glomeromycota: three new genera and glomoid species reorganized

Abstract: Species in the orders Glomerales and Diversisporales (Glomeromycetes) with glomoid spore formation are reorganized based on combined ribosomal sequence and morphological analyses. Within the Glomerales two genera in the Glomeraceae (Septoglomus, Simiglomus) and one genus in the Claroideoglomeraceae (Viscospora) are proposed as new. Paraglomerales species (thus far monogeneric) also form glomoid spores that may all germinate directly through the spore wall instead through subtending hyphae as in Glomerales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
71
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(79 citation statements)
references
References 18 publications
2
71
0
6
Order By: Relevance
“…Las esporas se fijaron permanentemente en una solución de PVLG (glicoglicerina de alcohol polivenilico). Con 400 x aumento en el microscopio de trasmision de luz se observaron las esporas y se clasificaron morfologicamente a nivel de género y especie, siguiendo la clasificación propuesta por Oehl et al (2011).…”
Section: Agroecosistema 2 (Denominado "Asociación Cacao-guaba Agr 2")unclassified
“…Las esporas se fijaron permanentemente en una solución de PVLG (glicoglicerina de alcohol polivenilico). Con 400 x aumento en el microscopio de trasmision de luz se observaron las esporas y se clasificaron morfologicamente a nivel de género y especie, siguiendo la clasificación propuesta por Oehl et al (2011).…”
Section: Agroecosistema 2 (Denominado "Asociación Cacao-guaba Agr 2")unclassified
“…and the Glomeromycotina (Schüßler and Walker 2010). In Glomus spp., all layers of the subtending hyphal wall and the spore wall form concurrently and the subtending hyphal wall layer continuous with the structural laminate spore wall layer arises far below the spore base and, thereby, the subtending hypha is persistent and its wall is colored similarly to the laminate spore wall layer (Oehl et al 2011b;Błaszkowski 2012). In contrast, the subtending hyphal wall of all Diversispora spp., also those with dark-colored spores, is hyaline to pale-colored and continuous only with a spore wall layer or layers overlying the main structural laminate spore wall layer, or the components of the subtending hyphal wall are continuous with all these spore wall layers (Oehl et al 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…In Glomus spp., all layers of the subtending hyphal wall and the spore wall form concurrently and the subtending hyphal wall layer continuous with the structural laminate spore wall layer arises far below the spore base and, thereby, the subtending hypha is persistent and its wall is colored similarly to the laminate spore wall layer (Oehl et al 2011b;Błaszkowski 2012). In contrast, the subtending hyphal wall of all Diversispora spp., also those with dark-colored spores, is hyaline to pale-colored and continuous only with a spore wall layer or layers overlying the main structural laminate spore wall layer, or the components of the subtending hyphal wall are continuous with all these spore wall layers (Oehl et al 2011b). However, the laminate spore wall layer probably arises de novo sequentially after the full differentiation of the spore wall layer(s), which cover them, and starts developing either at the level of the lower surface of the spore wall layer directly adhering to its upper surface or slightly below the spore base (Oehl et al 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…Nicolson) C. Walker, D. Still & A. Schüβler, originally described as G. viscosum T.H. Nicolson (Walker et al 1995) and erroneously transferred to a newly erected monospecific genus, Viscospora Sieverd., Oehl & G.A. Silva (Oehl et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, S. viscosum spores are hyaline to pale straw (http://invam.caf.wvu.edu/). Redecker et al (2013) concluded that the morphological features used to erect Septoglomus (Oehl et al 2011) are symplesiomorphies that can not define monophyletic groups.…”
Section: Introductionmentioning
confidence: 99%